Students’ thinking process in solving Pythagoras problems: Piaget’s theory in adversity quotient - Putri, Saskia Rizkiana; Fitriana, Laila; Kusmayadi, Tri Atmojo (UIN Raden Mas Said Surakarta, 2024)
Mathematics involves abstract concepts that require more than memorization; it demands a deep-thinking process for true understanding. This study aims to analyze and describe the thinking processes of students in solving problems related to the Pythagorean theorem, using Jean Piaget's theory in the context of Adversity Quotient (AQ). The research design is qualitative, employing a descriptive approach. The participants were 32 eighth-grade students from SMP Negeri 2 Ngawi, East Java province, Indonesia in the 2022/2023 academic year, categorized into three AQ groups: quitters, campers, and climbers. Data collection methods included the Adversity Response Profile (ARP) questionnaire, think-aloud tests, and interviews. The data were analyzed following Miles and Huberman’s model, which involves data reduction, presentation, and conclusion drawing. The results indicate: (1) Quitters displayed both assimilation and accommodation in understanding and planning problem-solving strategies, but relied on assimilation during problem-solving and review; (2) Campers primarily engaged in assimilation throughout understanding, planning, solving, and reviewing; (3) Climbers used assimilation for understanding, planning, and reviewing, but employed both assimilation and accommodation during problem-solving execution. These findings suggest that students' AQ levels influence their cognitive processes in mathematics problem-solving, with higher AQ individuals demonstrating greater flexibility in their thinking. This has implications for educators seeking to tailor instructional approaches to students' adversity responses, enhancing both cognitive development and resilience in learning.